AYO CEGAH DIABETES MELITUS MULAI DARI SEKARANG - Fitriyah, Nurul; Anggraini, Lisa Puji; Widya, Devi; Wijaya, Nusanta Adi; Hati, Anita Kumala; Dyahariesti, Niken (ABDI MAKARTI, 2025)
Risk factors for Diabetes Melitus disease are one of the comorbidities that worsen the condition of the elderly. Many people do not know and understand about Diabetes Mellitus. Therefore, the purpose of this Community Service (PKM) is designed to provide education and understanding to the community about Diabetes Mellitus. So it is hoped that this activity can increase public awareness about controlling Diabetes Mellitus. This PKM activity is carried out by providing educational counseling related to Diabetes Mellitus, checking blood sugar and blood pressure for free, then education related to compliance with how to take medication properly and correctly. This activity was attended by 22 residents from Ngablak village. The results of the activity showed that 4 people (18%) had confirmed that they had Diabetes Melitus and 18 people (81%) had normal blood sugar levels. Therefore, through this PKM activity, we carried out a health check-up program in the form of free blood sugar level checks and blood pressure checks and health education, especially Diabetes Mellitus. By carrying out this service, we hope that the problems in Ngablak Village, especially in the health sector, can be resolved a little